Examining Color Intensity Shift in Animated Films for the Development of the 'Color Script Generator' Application - Christian Aditya (Graduate School of Institut Seni Indonesia Yogyakarta, 2023)
This study aims to reveal the pattern of intensity shift in the color script following the Three act story structure of the animated film. Patterns of color palette changes can be found in each act of the story structure of an animated film. The dissemination of story structure in animated films affects the selection of color intensity used in the creation of color scripts. Visual observation will be done by measuring the intensity level of hue, saturation, and values from the color palette of scenes according to the act in several animated films with mainstream visual style. The observation results will produce a pattern of changes in the color palette on every scene that represents the idea of the story act. This pattern data can be used as a measurable system and as the basis for designing an application that can produce a color palette to support the creation of color scripts in animation.Â Meneliti Pergeseran Intensitas Warna dalam Film Animasi untuk Pengembangan Aplikasi 'Color Script Generator' Abstrak Penelitian ini bertujuan untuk mengungkap pola pergeseran intensitas pada color script mengikuti struktur cerita Tiga Babak dalam film animasi. Pola perubahan palet warna dapat ditemukan pada setiap babak struktur cerita sebuah film animasi. Dengan tersebarnya struktur cerita pada film animasi, hal ini memengaruhi pemilihan intensitas warna yang digunakan dalam pembuatan color script. Pengamatan visual akan dilakukan dengan mengukur tingkat intensitas hue, saturation, dan value dari palet warna yang sesuai dengan adegan di beberapa film animasi dengan gaya visual mainstream. Hasil observasi akan menghasilkan pola perubahan palet warna pada setiap adegan yang merepresentasikan ide dari adegan cerita. Data pola ini dapat digunakan sebagai sistem terukur dan berpotensi sebagai dasar perancangan aplikasi yang dapat menghasilkan palet warna untuk mendukung pembuatan color script dalam animasi.